Immunogenicity and Protective Efficacy of T-Cell Epitopes Derived From Potential Th1 Stimulatory Proteins of Leishmania (Leishmania) donovani - Joshi, Sumit; Yadav, Narendra Kumar; Rawat, Keerti; Kumar, Vikash; Ali, Rafat; Sahasrabuddhe, Amogh Anant; Siddiqi, Mohammad Imran; Haq, Wahajul; Sundar, Shyam; Dube, Anuradha (Frontiers in Immunology, 2019)
Development of a suitable vaccine against visceral leishmaniasis (VL), a fatal parasitic disease, is considered to be vital for maintaining the success of kala-azar control programs. The fact that Leishmania-infected individuals generate life-long immunity offers a viable proposition in this direction. Our prior studies demonstrated that T-helper1 (Th1) type of cellular response was generated by six potential recombinant proteins viz. elongation factor-2 (elF-2), enolase, aldolase, triose phosphate isomerase (TPI), protein disulfide isomerase (PDI) and p45, derived from a soluble antigenic fraction (89.9 to 97.1 kDa) of Leishmania (Leishmania) donovani promastigote, in treated Leishmania patients and hamsters and showed significant prophylactic potential against experimental VL. Moreover, since, it is well-known that our immune system, in general, triggers production of specific protective immunity in response to a small number of amino acids (peptide), this led to the identification of antigenic epitopes of the above-stated proteins utilizing immunoinformatics. Out of thirty-six, three peptides - P-10 (enolase), P-14 and P-15 (TPI) elicited common significant lymphoproliferative as well as Th1-biased cytokine responses both in golden hamsters and human subjects. Further, immunization with these peptides plus BCG offered 75% prophylactic efficacy with boosted cellular immune response in golden hamsters against Leishmania challenge which is indicative of their candidature as potential vaccine targets.